Socioeconomic inequalities in self-perceived oral health among adults in Chile. Issue 1 (December 2017) - Gallego, Francisco; Larroulet, Cristián; Palomer, Leonor; Repetto, Andrea; Verdugo, Diego
Abstract Background This paper studies the socioeconomic disparities in self-perceived oral health among Chilean adults and in the perceived physical, functional, psychological and social consequences of oral health. Methods In February 2011, 1, 413 residents of Metropolitan Area of Santiago, Chile, were interviewed using a standardized questionnaire and examined by dentists for dental status and oral health conditions. Only adults 18 to 60 years old affiliated with the public healthcare system were eligible to participate. We estimate socioeconomic gradients in self-perceived oral health and its distinct dimensions. We use the Heckman two-step procedure to control for selection bias given the non-random nature of the sample. In addition, we use a two-equation ordered response model given the discrete nature of the dependent variable. Results There is a non-linear socioeconomic gradient in self-perceived oral health even after controlling for oral health status. The gradient is steep at the lower end of the income distribution and constant at mid-income levels. These socioeconomic disparities are also found for the psychological and social dimensions of self-perceived oral health, but not for the functional limitations and physical pain dimensions. Conclusions The findings are consistent with inequities in the access to oral health services due to insufficient provision in the public sector and costly options in the private sector.